(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2024)
This article proposed a fresh reading of the coins of Fakhruddin Mubarak Shah to reappraise the political history of this ruler. In the light of recent numismatic sources the present research challenges all the earlier calculations of the reign period of Fakhruddin Mubarak Shah. In doing so this study makes an intervention in the political chronology of Bengal and proposes 205 (1333 to 1538 CE) years of Independent Sultanate Period instead of 200 (1338-1358 CE) years. What was the force behind the rise of Fakhruddin Mubarak Shah? What facilitated him to become an independent authority? In attempting to answer these question this article analyses the multi-dimensional factors - manmade and natural- that acted as catalysts in the making of Sonargaon as the first independent geo-political entity in the trans-Meghna region. Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 69(1), 2024, pp. 67-87